2008
DOI: 10.1186/1471-2253-8-1
|View full text |Cite
|
Sign up to set email alerts
|

A new analgesic method, two-minute sciatic nerve press, for immediate pain relief: a randomized trial

Abstract: BackgroundCurrent analgesics have drawbacks such as delays in acquisition, lag-times for effect, and side effects. We recently presented a preliminary report of a new analgesic method involving a two-minute sciatic nerve press, which resulted in immediate short-term relief of pain associated with dental and renal diseases. The present study investigated whether this technique was effective for pain associated with other disease types, and whether the relief was effective for up to one hour.MethodsThis randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…For the hand pressure method, a pressure of 10–20 kg/hand is required to provide pain relief [11–13]. The self‐administered method involves squatting down; therefore, the pressure to the sciatic nerve, per unit area, should be much smaller than the 10–20 kg/hand pressure administered by the hand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the hand pressure method, a pressure of 10–20 kg/hand is required to provide pain relief [11–13]. The self‐administered method involves squatting down; therefore, the pressure to the sciatic nerve, per unit area, should be much smaller than the 10–20 kg/hand pressure administered by the hand.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that acute pressure applied to the sciatic nerves can inhibit clinical pain, but not cold pressor pain [10][11][12][13]. Although the period of relief is short term, the relief from pain is significant; and the method can be used repeatedly (the analgesic effect decreases if repeated continuously) [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, chronic pressure applied to the sciatic nerve because of internal tension of the obturator muscle, or anatomical abnormalities in the piriformis muscle, can cause pain [6-8], and surgery to relieve pressure affords rapid relief [9-11]. On the contrary, we found that acute pressure applied to the sciatic nerve for 2 min provides rapid pain relief [4,5,12,13]. This relief is short-lived, with duration of minutes to hours.…”
Section: Introductionmentioning
confidence: 99%
“…This acupuncture point is located below the spinous process of the fourth lumbar vertebra, where branches of the sciatic nerve extend from the spinal cord (Figure 1). As seen in a few studies, effective pressure on any accessible area along the sciatic nerve will provide rapid pain relief, but the effectiveness is reduced if the pressure is applied distant from the sciatic nerve 6,7,9. Is the relief from sciatica pain attributable to stimulation of the acupuncture point or to stimulation of the sciatic nerve?…”
Section: Is There a Relationship Between Acupressure And Acute Pressumentioning
confidence: 99%
“…The method works well to alleviate various types of clinical pain but not experimental cold pressor pain or intense pain 6,7,9. Some physicians, patients, and scientists have interpreted this method as another approach for delivering the previously described analgesic method, acupressure.…”
Section: Introductionmentioning
confidence: 99%